Relationship of scapular dyskinesis with the pattern of activation of periescapular muscles during exercise - Spinoso, Deborah Hebling [UNESP]; Marin, Caroline Santos [UNESP]; Navega, Marcelo Tavella [UNESP] (FapUNIFESP (SciELO), 2022)
The aim of the present study was to analyze the activation pattern of the serratus anterior (SA), upper trapezius (UT), and lower trapezius (LT) muscles during periscapular exercises in individuals with and without ED, and to identify which proposed exercise presents greater activation of the periscapular muscles. Fourteen women, aged between 18 and 30 years, participated in this study, divided into a control group (n = 8) and a dyskinesis group (n = 8). The determination of the presence of ED was performed according to the analysis of scapular movement during arm elevation, using the yes/no classification. To evaluate muscle activation, electromyography signals of the SA, UT, and LT muscles were collected during exercise. The exercise protocol was composed of three repetitions of the exercises: punch up, wall slide, and scaption. The results showed that the ED group showed less activation of the AS and TT than the control group. During the scaption and wall slide exercises, the DE group showed less activation of the AS in relation to those without DE. There was no difference in muscle activation between the exercises. That individuals with dyskinesis have less activation of the muscles that control scapular mechanics and that the type of exercise did not influence the activation of the periscapular muscles.
Relação da discinese scapular com o padrão de ativação dos músculos periescapulares durante exercicios
Keywords: Electromyography; Exercise therapy; Scapula